New opportunities for the synthesis of quinoxaline derivatives - Olga S. Koptyaeva; Yuriy A. Azev; Yuriy M. Shafran; Tatyana A. Pospelova; Oleg N. Chupakhin (Chimica Techno Acta, 2019)
Convenient methods for the synthesis of quinoxaline derivatives with the use of nucleophilic aromatic substitution of hydrogen in heteroaromatic part of molecule in conditions of the acid catalysis were elaborated. The reactions of substitution of fluorine with amines in aromatic ring of 6,7-difluoroquinoxaline with the formation of monofluoro derivatives were studied.